2006
DOI: 10.4161/cbt.5.6.2708
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ADAM10 as a major source of HER2 ectodomain sheddase activity in HER2 overexpressing breast cancer cells

Abstract: Overexpression and activating mutations of ErbB family members have been implicated in the development and progression of a variety of tumor types. Cleavage of the HER2 receptor by an as yet unidentified ectodomain sheddase has been shown to liberate the HER2 extracellular domain (ECD) leaving a fragment with constitutive kinase activity that can provide ligand-independent growth and survival signals to the cell. This process is clinically relevant since HER2 ECD serum levels in metastatic breast cancer patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
132
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(139 citation statements)
references
References 33 publications
3
132
0
4
Order By: Relevance
“…Probably because of the generality of this type of endoproteolysis, it has been widely assumed that HER2 CTFs occurring in breast cancer patients arise exclusively through this mechanism. In accordance with this assumption, and despite the fact that they constitute a group of proteins ranging from ϳ90 to 120 kDa, HER2 CTFs are frequently referred to as P95 (6,23,33), the predicted molecular weight of the transmembrane product of HER2 ectodomain shedding. In a previous publication (1), we showed the existence of an additional mechanism of CTF generation, the alternative initiation of translation.…”
Section: Discussionmentioning
confidence: 97%
“…Probably because of the generality of this type of endoproteolysis, it has been widely assumed that HER2 CTFs occurring in breast cancer patients arise exclusively through this mechanism. In accordance with this assumption, and despite the fact that they constitute a group of proteins ranging from ϳ90 to 120 kDa, HER2 CTFs are frequently referred to as P95 (6,23,33), the predicted molecular weight of the transmembrane product of HER2 ectodomain shedding. In a previous publication (1), we showed the existence of an additional mechanism of CTF generation, the alternative initiation of translation.…”
Section: Discussionmentioning
confidence: 97%
“…Trastuzumab binding inhibits the proteolytic cleavage and shedding of HER2 by ADAM proteases (Molina et al, 2001;Liu et al, 2006). This may, in part, inhibit the invasive properties of HER2-transformed cells, since truncated HER2 induces a more invasive morphology and is associated with increased kinase activity, increased transforming efficiency, and is increased in patients with metastatic disease (Segatto et al, 1988;Christianson et al, 1998;Egeblad et al, 2001;Molina et al, 2002).…”
Section: Mechanism Of Action Of Trastuzumab -Inhibition Of Her2 Cleavagementioning
confidence: 99%
“…In addition to these fixation and antigen retrieval problems, the fact that TAAs can be modulated during the growth of tumor cells must be taken into consideration. 51,52 In this context, it was shown that extracellular receptor domains can be shed 53,54 and found in serum [55][56][57][58] or internalized into tumor cells. 59 Furthermore, different disintegrin and metalloproteinases (ADAMs), which are considered to be responsible for shedding, 60,61 can cleave antibodies, thereby compromising antitumoral efficacy.…”
Section: Discussionmentioning
confidence: 99%